2016
DOI: 10.1089/jpm.2015.0482
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Risk in Cancer Patients Undergoing Palliative Procedures by the American College of Surgeons Risk Calculator

Abstract: The ACSRC is a powerful tool for aid in surgical decision-making; however, in the case of palliative procedures for cancer patients, it overestimated the risk of postoperative complications and underestimated the LOS. Overestimation of post-operative complications could result in fewer patients being offered potentially beneficial palliative procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Currently, the ACS‐NSQIP surgical risk calculator may serve as a potential resource for this purpose. However, recent research investigating the reliability of the ACS‐NSQIP calculator for palliative surgeries in cancer patients has noted various limitations . For example, Rodriguez et al compared palliative surgery outcomes among cancer patients at a single institution to ACS‐NSQIP surgical risk calculator predicted outcomes and found that the ACS‐NSQIP risk calculator underestimated hospital length of stay and overestimated the risk of complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the ACS‐NSQIP surgical risk calculator may serve as a potential resource for this purpose. However, recent research investigating the reliability of the ACS‐NSQIP calculator for palliative surgeries in cancer patients has noted various limitations . For example, Rodriguez et al compared palliative surgery outcomes among cancer patients at a single institution to ACS‐NSQIP surgical risk calculator predicted outcomes and found that the ACS‐NSQIP risk calculator underestimated hospital length of stay and overestimated the risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research investigating the reliability of the ACS‐NSQIP calculator for palliative surgeries in cancer patients has noted various limitations . For example, Rodriguez et al compared palliative surgery outcomes among cancer patients at a single institution to ACS‐NSQIP surgical risk calculator predicted outcomes and found that the ACS‐NSQIP risk calculator underestimated hospital length of stay and overestimated the risk of complications. As our data and the Rodgriquez analysis demonstrates, DMa patients undergoing palliative surgical procedures consist of a unique patient population, and differences in patient demographics, frailty, and other undefined factors can significantly impact patient risk profiles and the predictive ability of various risk prediction models.…”
Section: Discussionmentioning
confidence: 99%
“…If a surgeon is willing to undertake a challenging procedure, the risk of complications is difficult to estimate; even a powerful tool like The American College of Surgeons Risk Calculator (ACSRC) in surgical decision-making for palliative procedures for cancer patients overestimates the risk of postoperative complications. It may underestimate length of stay [12], thus leading to even fewer patients being offered potentially beneficial palliative procedures.…”
Section: Discussionmentioning
confidence: 99%